Avoiding a “Death Panel” Redux - Piemonte, Nicole M. (The Hastings Center report, 2013)
If engaging in end of life conversations and advance care planning not only is desired by many Americans but also might significantly improve patient care at the end of life, then why was a provision that provided reimbursement for physicians to engage in end of life planning through Medicare removed from legislation? If, as some researchers have suggested, reimbursements under Medicare “would have been a start” for encouraging these conversations, then why was the Advance Care Planning Consultation provision in the 2008 health reform effort so vehemently opposed by politicians and citizens alike? The heated and misleading rhetoric employed against the ACPC undoubtedly contributed to intractable polarization surrounding this portion of the health reform bill and assured its failure. But the ACPC's emphasis on “checklists” and regulation may also have served as fodder for these fiery critiques. If that's right, legislation that focuses squarely on the broader and more fundamental goals of end of life consultations and deemphasizes administrative and documentary concerns may have a greater chance for success in years to come, as health reform is implemented and the battle over the ACPC fades from memory.